A numerical comparison of protective measures against external fire spread. (30th April 2018) - Nilsson, Markus; Husted, Bjarne; Mossberg, Axel; Anderson, Johan; McNamee, Robert Jansson
Summary: The impact of different passive protective measures against external vertical fire spread was investigated using the numerical tool Fire Dynamics Simulator (FDS). The numerical study was divided into a validation study and a comparative analysis. The validation study was performed to evaluate FDS as a calculation tool for modelling external vertical fire spread and was conducted using experimental results from a large‐scale fire test done on a SP FIRE 105 test rig at SP, Sweden. It was concluded that FDS 6.2.0 could reproduce the experimental results with a reasonable level of detail. In the comparative analysis, the impact on the external fire from a smaller apartment was studied in FDS with different configurations of horizontal projections and spandrels in the building exterior. Also, the effects of an upper and lower facade set‐back configuration were studied. The results show that facade solutions based on a horizontal projection or an upper facade set‐back configuration result in comparable or better protection compared with a defined spandrel height. The results also show that a spandrel height of at least 1.2 m can be replaced by a 60‐cm‐deep horizontal projection, given that the balcony is wider than the underlying opening.